2012
DOI: 10.1183/09031936.00210711
|View full text |Cite
|
Sign up to set email alerts
|

Serial computed tomography and lung function testing in pulmonary Langerhans’ cell histiocytosis

Abstract: Little is known about longitudinal lung function variation in patients with pulmonary Langerhans' cell histiocytosis (LCH). The contribution of serial lung computed tomography (CT) to managing these patients has not been evaluated.This long-term retrospective study included 49 patients who were serially evaluated by lung CT and pulmonary function tests. The lung function variation was categorised as improvement or deterioration. The extent of the CT lesions was correlated with lung function.Lung function deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 29 publications
4
76
0
16
Order By: Relevance
“…Also, previous study found that a lung CT at diagnosis of PLCH was informative (16) and confident (31,41). In the present study, not all the patients underwent tissue biopsy by open lung biopsy or thoracoscope, and this is a limitation of our study.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Also, previous study found that a lung CT at diagnosis of PLCH was informative (16) and confident (31,41). In the present study, not all the patients underwent tissue biopsy by open lung biopsy or thoracoscope, and this is a limitation of our study.…”
Section: Discussionmentioning
confidence: 57%
“…Serial lung function assessment is necessary for the follow-up of PLCH patients to identify their disease progression (28). However, in the current study, PFTs data during follow-up are not achieved, so a larger follow-up study is needed to prove the findings in the previous study (16).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Recent studies imply that cigarette smoking is an etiology of PLCH (2). Although smoking cessation's effect on the outcome of PLCH remains inconclusive, it is sometimes a reasonable option in some cases (2)(3)(4)(5). We herein discuss a case of PLCH that was complicated by severe pulmonary hypertension (PH) and respiratory impairment that dramatically improved after the patient stopped smoking.…”
Section: Introductionmentioning
confidence: 98%